(untitled) (European Journal of Pure and Applied Mathematics, 2021)
The main result of this paper is that: If R is a weak right PS-ring, then A = R[x; Î±, Î´], the Ore extension ring, is a weak right PS-ring whenever the following conditions hold on R is an (Î±, Î´)-compatible NI-ring with nil(R) nilpotent, Î±(e) = e and Î´(e) = 0 for every idempotent e âˆˆ R.